2014
DOI: 10.1177/0267659114527331
|View full text |Cite
|
Sign up to set email alerts
|

Increasing mean arterial pressure during cardiac surgery does not reduce the rate of postoperative acute kidney injury

Abstract: Maintaining a high level of MAP (on average) during normothermic CPB does not reduce the risk of postoperative AKI. It does not alter the length of hospital stay or the mortality rate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
43
1
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(48 citation statements)
references
References 39 publications
2
43
1
2
Order By: Relevance
“…During CPB, cardiac output is preserved, but the target blood pressure under such nonpulsatile conditions is unknown. A large RCT demonstrated that maintaining a higher level of mean arterial pressure during normothermic CPB did not reduce the incidence of AKI . However, before making any recommendations, further evidence is required.…”
Section: Resultsmentioning
confidence: 99%
“…During CPB, cardiac output is preserved, but the target blood pressure under such nonpulsatile conditions is unknown. A large RCT demonstrated that maintaining a higher level of mean arterial pressure during normothermic CPB did not reduce the incidence of AKI . However, before making any recommendations, further evidence is required.…”
Section: Resultsmentioning
confidence: 99%
“…Azau et al [25] recently published results of a single-center randomized controlled study of 300 patients with known risk factors for AKI undergoing elective cardiac surgery with normothermic CBP. In the control group, MAP during CPB was targeted to 50-60 mmHg, whereas in the intervention group, the target was 75-85 mmHg.…”
Section: Hypotension During Cardiopulmonary Bypassmentioning
confidence: 99%
“…[14] In addition to this study Azau and colleagues showed that an increased beset arterial pressure during CPB did not decrease the prevalence of acute kidney injury (AKI). [15] In a retrospective analysis that was published in 2008 that analyzed risk factors of gastrointestinal complications after cardiac surgeries, found that the decrease in blood flow and thus DO2 results in a state that the GI tract is not capable to recompense, because it doesn't have the ability of autoregulation. [16] Furthermore this state of hypoperfusion might be continued even after the re-establishment of adequate flows and pressures.…”
Section: Blood Flow During Cpb: Goals and Requirementsmentioning
confidence: 99%